2005
DOI: 10.1111/j.1095-8312.2005.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Different rewards in female and male flowers can explain the evolution of sexual dimorphism in plants

Abstract: Insects use floral signals to find rewards in flowers, transferring pollen in the process. In unisexual plants, the general view is that staminate (male) and pistillate (female) flowers obtain conspecific pollen transfers by advertising their rewards with similar floral signals. For female plants lacking food rewards, this can lead to floral mimicry and pollination by deceit. In this study, we challenge this view by presenting evidence for different rewards offered by flowers on females and males, as a mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 38 publications
1
33
1
Order By: Relevance
“…However, female inflorescences appear to offer no floral rewards to P. cinerascens. Hemborg and Bond (2005) thought that P. cinerascens were attracted to female L. xanthoconus inflorescences because they offered shelter, an essential resource not offered by male inflorescences. Our observations support this, in that the beetles hide between the inflorescence and the surrounding leaves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, female inflorescences appear to offer no floral rewards to P. cinerascens. Hemborg and Bond (2005) thought that P. cinerascens were attracted to female L. xanthoconus inflorescences because they offered shelter, an essential resource not offered by male inflorescences. Our observations support this, in that the beetles hide between the inflorescence and the surrounding leaves.…”
Section: Discussionmentioning
confidence: 99%
“…A small pollen beetle, Pria cinerascens Er. (Nitidulidae), is often associated with Leucadendron flowers, particularly the male inflorescences, where they feed on pollen and breed (Williams 1972;Hattingh and Giliomee 1989;Hemborg and Bond 2005). Williams (1972) suggested that at least six species are wind pollinated because of morphological changes such as a lack of conspicuous colored involucral leaves, a reduction of the hypogynous scale (nectaries), increased size of the female stigmatic surface, a lack of distinct floral odor, and showering of pollen when branches are shaken.…”
Section: Introductionmentioning
confidence: 99%
“…Pollination by beetles has been shown in a number of plants, most times in highly specialized relationships (Anstett, 1999;Franz, 2007;Gibernau et al, 1999;Hemborg and Bond, 2005;Ratnayake et al, 2006;Terry et al, 2005;Woitke et al, 2006). Nevertheless, generalist plants mostly pollinated by beetles have been also reported (Daphne laureola, Alonso, 2004;Romulea spp., Goldblatt et al, 2002;Shorea parviflora, Sakai et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, while many species of Leucadendron release their seeds from their ‘cones’ when they are mature, many others are strongly serotinous and maintain their seed bank in cones for several years before their release (Williams 1972). The causes of the often extreme sexual dimorphism displayed by some Leucadendron species has attracted a good deal of attention (Bond & Midgley 1988; Bond & Maze 1999; Hemborg & Bond 2005), but the possibility of an association between sexual dimorphism and serotiny, and its potential implications, has never been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Although little is known about the details of pollination in Leucadendron , some species are wind‐pollinated, while others are pollinated by insects (Rebelo 2001). Bond & Maze (1999) and Hemborg & Bond (2005) showed that pollinator visitation increased with ramification in males of L. xanthoconus , putatively because highly ramified males had more showy inflorescence displays (Bond & Midgley 1988). If selection on traits that influence siring success has contributed to the evolution of sexual dimorphism in Leucadendron , as these studies suggest, then one might expect an association between dimorphism and the pollination mode.…”
Section: Introductionmentioning
confidence: 99%